Identification, Characterization, and Preliminary X-ray Diffraction Analysis of a Single Stranded DNA Binding Protein (LjSSB) from Psychrophilic Lacinutrix jangbogonensis PAMC 27137 - Woong Choi; Jonghyeon Son; Aekyung Park; Hongshi Jin; Seung Chul Shin; Jun Hyuck Lee; T. Doohun Kim; Han-Woo Kim (Crystals, 2022)
Single-stranded DNA-binding proteins (SSBs) are essential for DNA metabolism, including repair and replication, in all organisms. SSBs have potential applications in molecular biology and in analytical methods. In this study, for the first time, we purified, structurally characterized, and analyzed psychrophilic SSB (LjSSB) from Lacinutrix jangbogonensis PAMC 27137 isolated from the Antarctic region. LjSSB has a relatively short amino acid sequence, consisting of 111 residues, with a molecular mass of 12.6 kDa. LjSSB protein was overexpressed in Escherichia coli BL21 (DE3) and analyzed for binding affinity using 20- and 35-mer deoxythymidine oligonucleotides (dT). In addition, the crystal structure of LjSSB at a resolution 2.6 Å was obtained. The LjSSB protein crystal belongs to the space group C222 with the unit cell parameters of a = 106.58 Å, b = 234.14 Å, c = 66.14 Å. The crystal structure was solved using molecular replacement, and subsequent iterative structure refinements and model building are currently under progress. Further, the complete structural information of LjSSB will provide a novel strategy for protein engineering and for the application on molecular biological techniques.